(untitled) (Third Sector Social Economic Review, 2023)
The golden rule of marketing is to understand human behavior and develop an effective strategy for the target audience. Marketers, who aim to meet the wishes and needs of consumers in the best way, benefit from the science of psychology in the stage of understanding and interpreting consumer psychology. In this sense, it is possible to state that the disciplines of marketing and psychology complement each other. In this study, bibliometric analysis of the articles published in the Journal of Psychology & Marketing between 2019-2022 was conducted in order to identify current research in the fields of marketing and psychology and to shed light on future research. The data within the scope of the research were obtained from the Web of Science database and were analyzed using the Vosviewer software. As a result of the analysis, it was seen that the most cited authors in P&M were ’Moriuchi, E’, ’Dwivedi, YK’, ’Marriott, HR’, ’Wang I’, ’de Angelis, M’. It has been determined that the most influential institutions are ’The Hong Kong Polytechnic University’, ’Auckland University of Technology’, ’University of Portsmouth’, ’University of Texas at Austin’ and ‘Bournemouth University’. It was concluded that the most frequently used keywords were ’Artificial Intelligence’, ’Social Media’, ’Covid-19’, ’Sustainability’, ’Anger’, ’Consumer Behavior’, ’Donation’ and ’Anthropomorphism’.